THE IMPORTANCE OF CLASSROOM MANAGEMENT IN TEACHING MIXED-ABILITY CLASSES - Zulfizar Qo’chqorova; Gulrukh Nizomidinova (Лучшие интеллектуальные исследования, 2023)
Abstract: The given article presents the problems that arise with classroom management in teaching pupils of different levels with many teachers today. The research conducted by various scientists on teaching mixed-ability classes was learned and analyzed, and then solutions to the problems were found. If students of different levels are gathered in one class, classroom management was found to be important in increasing the effectiveness of their learning. Also, the work includes some suggestions for teachers in teaching mixed-ability classes.